Challenges of scaling-up of TB-HIV integrated service delivery in Ghana. - Prince Justin Anku; Joshua Amo-Adjei; David Doku; Akwasi Kumi-Kyereme (PLoS ONE)
Integration of tuberculosis and HIV services in many resource-limited settings, including Ghana, has been far from optimal despite the existence of policy frameworks for integration. A previous study among programme managers and other stakeholders at the national level has documented tardiness in committing to the integration of services. In this paper, we aimed at unravelling pertinent challenges that confront TB-HIV integrated service delivery. Data were obtained from interviews with 31 individual health care providers operating under different models of TB-HIV service delivery. The study is framed around the Complexity Theory. We applied inductive and deductive techniques to code the data and validations were done through inter-rater mechanisms. The analysis was done with the assistance of QSR NVivo version 12. We found evidence of a convivial working relationship between TB-HIV service providers at the facility level. However, the interactions vary across models of care-the lesser the level of integration, the lesser the complexities for interactions that ensued. This had resulted in operational challenges on account of how the two-disease environment interacts with the other components of the health system. These challenges included; weak/inappropriate infrastructure, frail coordination between the two programmes and hospital administrators, under-staffing in comprehensive TB-HIV management, use of community facility under the Directly-Observed Treatment (DOT) protocols, and financial constraints. To fully appropriate the enormous benefits of TB-HIV service integration, there is a need to address these challenges.